Evolutionary implications of variation in the calling song of the cricket Gryllus bimaculatus De Geer (Orthoptera : Gryllidae) - Ferguson, J. Willem H. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2006.